Portable Deep Learning-Driven Ion-Sensitive Field-Effect Transistor Scheme for Measurement of Carbaryl Pesticide - Nongluck Houngkamhang; Pattarapong Phasukkit (My University, 2022)
This research proposes a multiple-input deep learning-driven ion-sensitive field-effect transistor (ISFET) scheme to predict the concentrations of carbaryl pesticide. In the study, the carbaryl concentrations are varied between 1 × 1
Keywords: ISFET; Carbaryl; Analytical Chemistry and Sensors